Developing Hidden Questions as a Learning Model to Enhance Student Communication Skills - Ridwan Santoso; Lucky Nadya; Mukhammad Murdiono (Bulletin of Social Studies and Community Development, 2023)
Abstract: Developing Hidden Questions As A Learning Model To Enhance Student Communication Skills. This study was designed to develop learning models to improve student communication skills. In a learning model called hidden questions, students are required to learn actively through an exercise of arguing and answering questions. This R and D (research and development) study followed the instructional design proposed by the ADDIE (Analysis, Design, Development, Implementation and Evaluation) framework. The data were obtained from expert validation, interviews and model implementation in junior high schools in Pringsewu District, Indonesia, and analysed by a mixed method of quantitative (Test Statistics Kruskal Wallis) and descriptive qualitative. The results of the Test Statistics Kruskal Wallis showed that the asymptotic significance or p-value was 0.001 less than 0.05, indicating statistically significant differences between before and after the model implementation or signifying that the hypothesis is accepted. The quantitative and qualitative data analysis revealed that hidden question created an effective learning model in improving student communication skills. These findings provide a basis for further research in the development of learning models that can improve Communication, Collaborative ability, Critical Thinking and Creativity skills of students. Keywords: learning model, hidden questions, questions and answers, communication skills DOI: http://dx.doi.org/10.61436/bsscd/v2i1.pp11-25